2007
DOI: 10.1111/j.1538-7836.2007.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of plasma tissue factor and tissue factor pathway inhibitor for cardiovascular death in patients with coronary artery disease: the AtheroGene study

Abstract: Vague I, Tiret L, for the AtheroGene Investigators. Prognostic value of plasma tissue factor and tissue factor pathway inhibitor for cardiovascular death in patients with coronary artery disease: the AtheroGene study. J Thromb Haemost 2007; 5: 475-82.See also Toschi V. Soluble tissue factor and tissue factor pathway inhibitor in cardiovascular disease. This issue, pp 472-4.Summary. Background: Tissue factor (TF) and its specific inhibitor, tissue factor pathway inhibitor (TFPI), are important contributors to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…15,20 Levels of free TFPI have been reported to be elevated in acute myocardial ischemia. 23 In our numerical simulations, the collective contributions of AT, fII, and fVIII were most prominent. 22 In this study, we have evaluated the potential for alteration of the systemic coagulation system in ACS by studying injury to the peripheral microcirculation in non-anticoagulated patients undergoing AMI and compared their response to a control cohort with stable coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 95%
“…15,20 Levels of free TFPI have been reported to be elevated in acute myocardial ischemia. 23 In our numerical simulations, the collective contributions of AT, fII, and fVIII were most prominent. 22 In this study, we have evaluated the potential for alteration of the systemic coagulation system in ACS by studying injury to the peripheral microcirculation in non-anticoagulated patients undergoing AMI and compared their response to a control cohort with stable coronary artery disease (CAD).…”
Section: Introductionmentioning
confidence: 95%
“…The secreted TFPI from monocytes and most vascular wall cells may be associated within plaque through the binding with proteoglycans and other TFPI binding protein on the cells (30,31). It has been reported in literature to be elevated in AMI patients (5,(7)(8)(9). Our results indicate increase levels in younger AMI patients while insignificant changes in the levels of plasma TFPI in elder AMI patients as compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described the role of the polymorphism +5466 A/G of the TF gene, showing that it is associated with the risk of thrombosis (Reny et al, 2004;Mälarstig et al, 2005;Morange et al, 2007;Davis and Erlich, 2008;Boles and Mackman, 2010) and a threefold increase in the risk of thrombosis in individuals that possess this polymorphism (Opstad et al, 2010a). Thus, several studies have reported the relationship between this polymorphism and regulation of TF expression and high levels of TF in cardiovascular disease (Campo et al, 2006;Undas et al, 2009;Opstad et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%